بناء نموذج ریاضی للتنبؤ بالرحلات المتولدة لمدینة الرمادی - nan, nan (Iraqi Journal of Civil Engineering, 2007)
Ramadi city is one of the cities that become need to Transportation planning studies , so its, last time have increase in population changed in social and economic state and have increasing in number of moving vehicles و which causes jamming in transportation network. For the purpose of study, the city was divided into 18 zones and data was collected through this zone. Data was related to socioeconomic characteristics of the population and field surveys were done for the base year (2000). The study has achieved building trip production model in Ramadi city, through find relationship between socioeconomic characteristics (car ownership, family income, employee no. , family no. , population, family size, time and cost trip, distance to the center and area of the dwelling). It was found that the number of families is the most influential variable to trip production model.